[Building Off Eldfell From Window] - Streng, Evelyn Fiedler (1975)
Photograph of a building along Eldfell from a broken window. The shattered window is surrounded by brown, wooden plants and a dirty white frame and walls. Black dirt dotted in green plants is visible through the window frame to the right, leading to the rectangular, white building with a red roof at the foot of the mountain behind it.